PENGARUH PENGGUNAAN TEKNIK PEMODELAN BERBASIS MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 15 PADANG - Zulfikarni, Sofya Nofrita, Yasnur Asri, (Universitas Negeri Padang, 2017)
This article aim to find out the effect of modeling technique based on problem based learning method toward news writing skill for student at class VIII SMPN 15 Padang. Data in this study was score of news writing skill. Data was obtained by testing student to write news before and after application of problem based learning model at school. News writing skill before and after application of problem based learning model was compared to see the effect of the model by use of t-test equation. Study fining showed that: 1) news writing skill before application of problem based learning model was in level of above-moderate; 2) news writing skill after application of problem based learning model was in level of good; and 3) based on t-test, it was concluded that there was a significant effect of problem based learning model toward news writing skill for student at class VIII SMPN 15 Padang. Kata Kunci: Pengaruh, Teknik pemodelan berbasis model Problem Based Learning, Keterampilan menulis berita.